Caracterización morfoagronómica y de rendimiento en cuatro variedades de yuca para producción de almidón. Zungarococha. San juan. 2024 - Hernandez Delgado, Yani Yane (2025)
The objective of the research work was to characterize morpho-agronomically four varieties of cassava for industrial purposes. Due to its approach, it was quantitative, prospective, descriptive level and experimental research design. The target population of the study consisted of four varieties of cassava from the community of San José de Lupuna. Amazonas River. The experimental design was Randomized Complete Blocks (DBCA) with four repetitions. The list of descriptors used was from FUKUDA W.M.G and GUEVARA (1988). The data obtained were analyzed through the R Software and the R Studio graphical interface version 4.4.1. Among the main conclusions obtained were that there is high morphological variability among cassava varieties: The four varieties of Manihot esculenta (Mandioca, Lovera, Yuca Negra and Pisco) present a notable diversity in the qualitative descriptors of the plant, stem, leaf, flower, fruit and root. The Jaccard distance and multiple correspondence analyses confirm that the four cassava varieties are clearly differentiated in terms of their highly discriminating morphological characteristics, such as the Lovera variety showing distinctive characteristics such as the presence of flowers and specific colors, while Yuca Negra stood out for its leaf shape and pulp characteristics. Significant correlations were observed between quantitative descriptors such as plant height and height at first branch, suggesting that they can be used as morphological markers for indirect selection, as well as to predict others related to productivity or genetic resistance to biotic or abiotic factors. Principal component analysis (PCA) demonstrates that quantitative descriptors related to roots and leaves have a high discriminating power between varieties, contributing significantly to the variability of the cassava varieties studied. In particular, root length and leaf lobe width were key quantitative descriptors in the differentiation between varieties